Personality and psychological health in caregivers of older relatives: a case-control study. (2nd September 2021) - Luchetti, Martina; Terracciano, Antonio; Stephan, Yannick; Aschwanden, Damaris; Sutin, Angelina R.
Abstract: Objectives: Being a caregiver of an older adult is often associated with poor psychological outcomes and stress. Individual differences, such as personality, may moderate responses to caregiving. In this study, we examined (a) personality and psychological health of family caregivers compared to non-caregivers and (b) tested interactions between caregiver status and personality (both domains and facets) in predicting psychological outcomes. Methods: Data were from an online sample of caregivers of older relatives ( N  = 491; 71.9% females) and matched controls ( N  = 491). Participants completed the Big Five Inventory-2 and a comprehensive set of psychological health and well-being measures. Results: Compared to non-caregivers, caregivers had higher neuroticism, lower energy level (extraversion facet) and higher compassion (agreeableness facet). They also reported higher depression, anxiety, loneliness, and lower well-being and life satisfaction. Personality traits and facets had strong associations with psychological outcomes, and these associations were similar across the two groups. Only a few significant interactions between caregiver status and personality were found: For instance, higher neuroticism (in particular, higher scores on anxiety and depression facets) exacerbated anxiety among caregivers. Conclusions: Personality is a relevant correlate of psychological health. In the context of caregiving, its assessment may help to identify caregivers at risk of poor outcomes and inform intervention programs. Further research is needed to replicate the findings and investigate longitudinal interrelations among variables.